Srebrenica – Triumph of Evil - Vidaković, Mina; Klarin, Mirko (Sense Production, 2001)
Duration: 01:30:00 Produced by SENSE Agency (based in The Hague, ICTY) this documentary about the Srebrenica Trial is the first video-document about a complete trial before an international criminal tribunal after WWII.